AKIBAT HUKUM PRAKTIK JUAL RUGI SEMEN CONCH DALAM PERSAINGAN USAHA INDUSTRI SEMEN DI INDONESIA - Wahyu Buana Putra; Teddy Prima Anggriawan; Aldira Mara Ditta Caesar Purwanto (Pusat Riset dan Inovasi Nasional, 2023)
Competition in the business world has various ways by each business actor. Judging from the application of the principles of business competition in Indonesia, there are several rules that contain matters in carrying out the business world. All provisions contained in the laws and regulations regulate the rights and obligations of every business actor in running his business. Given the content of Law No. 5/1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition describes several actions or practices that are prohibited in competing to develop the business of every business actor in Indonesia. One of the prohibitions in the world of business competition is the practice of predatory pricing or commonly referred to as the act of selling at a loss. This practice is an act of selling products from production at prices far below the proper average. This study will discuss one of the case studies related to selling at a loss that occurred in the cement industry in Indonesia, especially in the province of South Kalimantan. Cement Conch which is a product of PT. Conch Cement was the party that was reported on the grounds that there was an alleged monopoly action in the form of a loss-selling practice. Conch cement companies are reported under the provisions of the article in the business competition law. In accordance with the KPPU's decision issued, stated that conch cement was proven to have carried out this practice. Regarding monopoly practices carried out by conch cement companies, we will review the legal consequences and responsibilities based on the applicable laws and regulations.